THE URGENCY OF A VICTIM-ORIENTED APPROACH TO ADDRESS THE VACUUM OF SUBSTANTIVE JUSTICE IN CANING SENTENCES FOR SEXUAL HARASSMENT CASES IN ACEH - Ahmad Fizal; Eka Nurhidayat; Ade Faiza; Jailani Jailani (Journal of Social Science, 2026)
Objective: The implementation of special autonomy authority in Aceh Province through the application of Qanun Number 6 of 2014 concerning Jinayat Law has raised dynamics in law enforcement, particularly in handling sexual harassment cases. The sentencing practice that focuses on inflicting physical punishment in the form of caning (offender-oriented) is considered to leave a vacuum in providing guarantees of substantive justice for the victims. This study aims to examine three main issues: (1) the proportionality of caning for perpetrators of sexual harassment when viewed from substantive justice for the victims; (2) the implications of enforcing the Jinayat Qanun on the victims' right to feel safe and human rights protection; and (3) the idea of reconstructing the enforcement of jinayat law to be oriented towards victim recovery (victim-oriented). Method: This study uses a normative legal research method through a statute approach and a conceptual approach. Data collection was carried out through library research on laws and regulations, court decisions, human rights instruments, and academic literature, which were then analyzed qualitatively-descriptively. Results: The results of the study indicate that, first, the imposition of caning in sexual harassment cases is not proportional to the victim's suffering. The short-lived physical execution is considered disproportionate to the long-term psychological trauma experienced by the victim, thus failing to fulfill the element of substantive justice. Second, the current enforcement of jinayat law is not yet optimal in accommodating the fundamental rights of the victims, especially the recovery instruments and the fulfillment of the right to feel safe and protected as mandated by the constitution. Novelty: Third, it is necessary to reconstruct the paradigm of Islamic criminal law in Aceh by adopting victimological principles, where the orientation of sentencing must not stop at mere physical punishment, but must be integrated with the obligation of restitution and psychological rehabilitation that guarantees the full recovery of the victims.